Perspectives for a China Strategy - Nye, Joseph S. (PRISM, 2020)
When the Munich Security Conference met in February 2020, China was the most frequently mentioned country, while there was an exaggerated mood of Western decline. Yet as the recent COVID-19 pandemic has shown, China has both strengths and weaknesses. Its initial censorship, suppression of feedback and curtailment of international information allowed the pandemic to develop and fester. Draconian quarantine of Wuhan curtailed its spread somewhat; followed by a government propaganda campaign to attract others to the theme that China's behavior had been benign. When the pandemic eventually subsides, however, China will be faced with the political and economic costs resulting from the exposure of both a failed public health system and an overly rigid party control system.